Tackling youth unemployment in East-Central Europe - Kenneth Roberts; Colette Fagan; Klara Foti; Bohdan H. Jung; Sijka Kovačeva; Ladislav Macháček (Journal for East European Management Studies, 1999)
This paper draws upon evidence from survey research in Bulgaria, Hungary, Poland and Slovakia to describe how young people's old routes into the labour markets in East-Central Europe have disintegrated in the 1990s while new routes and career groups have been created. A typology of these new routes is constructed and is then used to explain how and why levels of youth unemployment have risen and refuse to fall even in countries where, according to official economic statistics, recovery is now well-advanced, and despite the introduction of active labour market measures. It is concluded that levels of youth unemployment will subside, and prevent the creation of excluded groups, only if the development of the new market economies is managed. – – Diese Studie basiert auf Umfrageergebnissen aus Bulgarien, Ungarn, Polen und der Slowakei. Es wird gezeigt, wie herkömmliche Wege in den Arbeitsmarkt für junge Leute versagen und sich neue Wege und Karrieremöglichkeiten eröffnen. Es wird eine Typologie dieser neuen Wege konstruiert, mit deren Hilfe erklärt werden kann, warum die Jugendarbeitslosigkeitsrate steigt und warum sie selbst in solchen Ländern nicht fällt, in denen die wirtschaftliche Erholung fortgeschritten ist und wo drastische Maßnahmen zur Arbeitsbeschaffung unternommen werden. Es wird geschlossen, daß die Jugendarbeitslosigkeit nur dann unter Kontrolle zu bekommen ist, wenn die Entwicklung junger Marktwirtschaften erfolgreich verläuft.
Keywords: 650